Diversity of Siphonophora (Cnidaria: Hydrozoa) in the Western Caribbean Sea: new records from deep-water trawls - Gasca, Rebeca (Zootaxa, 2009)
Siphonophores are one of the least known gelatinous zooplankters in the tropical waters of the Northwestern Atlantic. Most of the regional knowledge about their diversity and distribution is based on surface samples (0–200 m). Siphonophores were collected from oceanic waters off the Mexican Caribbean across an expanded sampling range (0–940 m) during two cruises and were taxonomically examined. A total of 47 siphonophore species were recorded, of these, 14 had not been found in this sector of the Caribbean Sea and 10 represent new records for the Caribbean Basin. The number of species currently known from the western Caribbean is increased from 42 to 56. Some of these species also represent new records for the Northwestern Tropical Atlantic region. The greatest relative increase was observed among species of Lensia, five of which are exclusively deep-living forms dwelling below 300 m. A revised, expanded checklist of the siphonophores of the Western Caribbean is also provided. These results confirm the need of further deep sampling to increase our understanding of Caribbean siphonophore diversity.